2019
DOI: 10.3390/ijms20123025
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Hybrid Protein from Dermatophagoides pteronyssinus Allergens Shows Hypoallergenicity

Abstract: The house dust mite (HDM) Dermatophagoides pteronyssinus is an important risk factor for asthma and rhinitis. Allergen specific immunotherapy that is based on recombinant proteins has been proposed for the safer and more efficient treatment of allergic diseases. The aim of this study was to design and obtain a hybrid protein (DPx4) containing antigenic regions of allergens Der p 1, Der p 2, Der p 7, and Der p 10 from this mite. DPx4 was produced in Escherichia coli and its folding was determined by circular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(69 reference statements)
4
6
0
Order By: Relevance
“…Despite their efficacy in decreasing asthma features, allergen-derived peptides may also be improved. Indeed, Martıńez and colleagues showed that the combination of several Der p allergen-derived peptides exhibits anti-inflammatory properties (52). Moreover, the use of nanoparticles as adjuvants (53) in allergen-derived peptide immunotherapy could potentially improve their ability to polarize innate and adaptive cells into a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their efficacy in decreasing asthma features, allergen-derived peptides may also be improved. Indeed, Martıńez and colleagues showed that the combination of several Der p allergen-derived peptides exhibits anti-inflammatory properties (52). Moreover, the use of nanoparticles as adjuvants (53) in allergen-derived peptide immunotherapy could potentially improve their ability to polarize innate and adaptive cells into a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For example, basophil activation experiments demonstrated that a hybrid consisting of major allergens from two different aeroallergen sources, Bet v 1 and Phl p 5 induced a much reduced activation, compared with the monomeric forms of the proteins [ 68 ]. Similarly, fusion proteins consisting of four antigenic regions from the major allergens of the mite species D. pteronyssinus showed a significantly reduced IgE reactivity, compared with the individual proteins (Der p 1, Der p 2 and Der p 7) [ 69 ]. Mice immunized with the HDM hybrid protein generated blocking IgG antibodies, thus showing a possibility for a novel HDM vaccine [ 69 ].…”
Section: Recombinant Hypoallergenic Moleculesmentioning
confidence: 99%
“…Similarly, fusion proteins consisting of four antigenic regions from the major allergens of the mite species D. pteronyssinus showed a significantly reduced IgE reactivity, compared with the individual proteins (Der p 1, Der p 2 and Der p 7) [ 69 ]. Mice immunized with the HDM hybrid protein generated blocking IgG antibodies, thus showing a possibility for a novel HDM vaccine [ 69 ].…”
Section: Recombinant Hypoallergenic Moleculesmentioning
confidence: 99%
“…Allergen-induced upregulation of CD203c was expressed as the stimulation index (SI), calculated using mean fluorescence intensities (MFI) obtained with stimulated sample (MFI stim) divided by unstimulated sample (MFI control), SI = MFI stim/MFI control. SI ≥ 2.0 was considered positive [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%